Financial incentives, contraceptive use and abortion behavior - Mathilde Almlund; Mette Ejrnæs; Thomas H. Jørgensen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2025)
We examine whether financial incentives affect fertility and family planning. We use a reform reducing child benefits paid to larger families together with Danish longitudinal register data on the universe of legal abortions and birth control pill purchases to address this question. We find that partnered women in low-income households reduced their fertility in response to the reform, partly by increasing the use of abortions. Younger women also increased the use of oral contraceptives. Responses are largest for younger and cohabiting women compared to their married counterparts. Our results show that family policies can affect family planning through financial incentives.
Keywords: J13; I38; J16; 330; Childbirth; Abortion; Birth control; The Pill; Child Benefits